EXPRESSION OF THE NEURAL CELL ADHESION MOLECULE IN THE RENAL INTERSTITIUM IN DIFFERENT STAGES OF FIBROSIS - Mioljević, Ana; Filipović, Isidora; Nikolić, Gorana; Janković, Aleksandar; Bogosavljević, Nikola; Đurić, Petar; Boričić, Novica; Životić, Maja (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: In healthy adult kidneys, differentiated tubular epithelial cells do not express the neural cell adhesion molecule (NCAM), while a small number of NCAM-expressing cells can be detected in the renal interstitium. The role and the significance of these cells have not yet been clarified, but it has been observed that the number of NCAM-expressing cells increases in the initial stage of interstitial fibrosis.Aim: The aim of the study is to examine the significance of the expression of NCAM molecules in the renal interstitium, in etiologically different diseases, with varying degrees of interstitial fibrosis, as well as to define the pathohistological and clinical indicators (predictors) of impaired kidney function.Materials and methods: The study included 69 patients who underwent needle biopsies of the kidneys in 2011 and 2012. Clinical and laboratory data were collected at the time of the biopsy and at the time of the latest follow-up examination. Pathohistological characteristics were defined optically-microscopically, while NCAM-expressing interstitial cells were detected with immunohistochemical staining, using the primary NCAM antibody (1:50, clone 123C3.D5).Results: NCAM-expressing interstitial cells were detected in 59.4% of kidney biopsies, the presence of these cells was significantly more frequent in the initial stages of interstitial fibrosis than in the remaining stages (p < 0.001), and it did not depend on the pathohistological diagnosis (p = 0.995). Patients in whom NCAM cells were detected had significantly lower proteinuria levels at the time of biopsy, as compared to patients without NCAM interstitial cells (p = 0.024). The levels of serum creatinine (p < 0.001) and urea (p = 0.007) significantly influenced the probability of the deterioration of renal function.Conclusion: The presence of NCAM cells in the kidney interstitium is a characteristic of the early stages of chronic kidney disease with incipient interstitial fibrosis and a lesser degree of proteinuria.
Keywords: NCAM-expressing renal interstitial cells; interstitial fibrosis; renal impairment; predictors